Effects of resisted sprint training on sprint, jump, and change-of-direction performance in athletes: a systematic review and meta-analysis - Li, C.; Chen, L.; Zhang, Q. (Frontiers in Physiology, 2025)
Objective: To systematically evaluate the effects of RST (resisted sprint training) on athletes` sprint, jump, and COD (change-of-direction performance).